Persuasive Technology 5th International Conference, PERSUASIVE 2010, Copenhagen, Denmark, June 7-10, 2010. Proceedings - Ploug, Thomas; Hasle, Per.; Oinas-Kukkonen, Harri; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 5th International Conference on Persuasive Technology, PERSUASIVE 2010, held in Copenhagen Denmark in June 2010. The 25 papers presented were carefully reviewed and selected from 80 submissions. In addition three keynote papers are included in this volume. The topics covered are emotions and user experience, ambient persuasive systems, persuasive design, persuasion profiles, designing for health, psychology of persuasion, embodied and conversational agents, economic incentives, and future directions for persuasive technology.
Technology for Changing Feelings -- I Persuade, They Persuade, It Persuades! -- Behavior Change Support Systems: A Research Model and Agenda -- Persuasive Conversational Agent with Persuasion Tactics -- Happier Together: Integrating a Wellness Application into a Social Network Site -- Animate Objects: How Physical Motion Encourages Public Interaction -- What Makes Social Feedback from a Robot Work? Disentangling the Effect of Speech, Physical Appearance and Evaluation -- The Persuasive Power of Virtual Reality: Effects of Simulated Human Distress on Attitudes towards Fire Safety -- Successful Persuasive Technology for Behavior Reduction: Mapping to Fogg$1 (Bs Gray Behavior Grid -- Selecting Effective Means to Any End: Futures and Ethics of Persuasion Profiling -- Individual Differences in Persuadability in the Health Promotion Domain -- Designing for Persuasion: Toward Ambient Eco-Visualization for Awareness -- Behavior Wizard: A Method for Matching Target Behaviors with Solutions -- Ambient Persuasive Technology Needs Little Cognitive Effort: The Differential Effects of Cognitive Load on Lighting Feedback versus Factual Feedback -- Design Dimensions Enabling Divergent Behaviour across Physical, Digital, and Social Library Interfaces -- Personality and Persuasive Technology: An Exploratory Study on Health-Promoting Mobile Applications -- Persuasive Features in Six Weight Loss Websites: A Qualitative Evaluation -- The Dominant Robot: Threatening Robots Cause Psychological Reactance, Especially When They Have Incongruent Goals -- Practical Findings from Applying the PSD Model for Evaluating Software Design Specifications -- Activity-Based Micro-pricing: Realizing Sustainable Behavior Changes through Economic Incentives -- Enhancing Human Responses to Climate Change Risks through Simulated Flooding Experiences -- Pitfalls in Persuasion: How Do Users Experience Persuasive Techniques in a Web Service? -- Using Persuasive Design Principles in Motivational Feeling towards Children Dental Anxiety (CDA) -- Facilitation of Goal-Setting and Follow-Up in an Internet Intervention for Health and Wellness -- Persuasive Dialogue Based on a Narrative Theory: An ECA Implementation -- Generating Directions for Persuasive Technology Design with the Inspiration Card Workshop -- Designing Effective Persuasive Systems Utilizing the Power of Entanglement: Communication Channel, Strategy and Affect -- Embodied Agents, E-SQ and Stickiness: Improving Existing Cognitive and Affective Models.s
Keywords: Computer science; Information storage and retrieval systems; Information systems; Artificial intelligence; Social sciences -- Data processing; Education; Computer Science; Computers and Education; Information Systems Applications (incl.Internet).; User Interfaces and Human Computer Interaction; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Computer Appl. in Social and Behavioral Sciences